QORAQALPOG‘ISTONNING MUHIM ORNITOLOGIK HUDUDLARI VA ULARNING QUSHLARNI MUHOFAZA QILISHDAGI AHAMIYATI - Ametov Y.I., Ametov Y.I.; Mambetkarimova G.K., Mambetkarimova G.K.; Abdikarimova M.K, Abdikarimova M.K; Orinbayev D.J., Orinbayev D.J.; Abdireymova N.B., Abdireymova N.B. (Actual problems and prospects of the study of the fauna, 2024)
Currently, 177 species of birds belonging to 17 genera and 42 families have been found to live in Jiltirbas Lake and its surroundings. 20 species of common species are included in the Red Book of the Republic of Uzbekistan, 8 of them are included in the Red List of the International Threatened Species. These are: pink merganser Pelecanus onocrotalus, lesser black grebe Phalacrocorax pygmeus, white-tailed goose Anser erythropus, white-eyed goose Aythya nyroca, mallard Oxyura leucocephala, common grebe Circus macrourus, long-tailed osprey Haliaeetus leucoryphus and white-tailed osprey Haliaeetus albicilla.